Answer
Here are the solutions by completing the square:
1) \( p = -7 \pm \sqrt{87} \)
3) \( a = -7 \pm 10 \) (which simplifies to \( a = -17 \) and \( a = 3 \))
5) \( x = -3 \pm 1 \) (which simplifies to \( x = -4 \) and \( x = -2 \))
7) \( x = -7 \pm 8 \) (which simplifies to \( x = -15 \) and \( x = 1 \))
Solution
Solve the quadratic equation by following steps:
- step0: Solve by factoring:
\(x^{2}+14x-15=0\)
- step1: Factor the expression:
\(\left(x-1\right)\left(x+15\right)=0\)
- step2: Separate into possible cases:
\(\begin{align}&x-1=0\\&x+15=0\end{align}\)
- step3: Solve the equation:
\(\begin{align}&x=1\\&x=-15\end{align}\)
- step4: Rewrite:
\(x_{1}=-15,x_{2}=1\)
Solve the equation \( a^{2}+14 a-51=0 \).
Solve the quadratic equation by following steps:
- step0: Solve by factoring:
\(a^{2}+14a-51=0\)
- step1: Factor the expression:
\(\left(a-3\right)\left(a+17\right)=0\)
- step2: Separate into possible cases:
\(\begin{align}&a-3=0\\&a+17=0\end{align}\)
- step3: Solve the equation:
\(\begin{align}&a=3\\&a=-17\end{align}\)
- step4: Rewrite:
\(a_{1}=-17,a_{2}=3\)
Solve the equation \( x^{2}+6 x+8=0 \).
Solve the quadratic equation by following steps:
- step0: Solve by factoring:
\(x^{2}+6x+8=0\)
- step1: Factor the expression:
\(\left(x+2\right)\left(x+4\right)=0\)
- step2: Separate into possible cases:
\(\begin{align}&x+2=0\\&x+4=0\end{align}\)
- step3: Solve the equation:
\(\begin{align}&x=-2\\&x=-4\end{align}\)
- step4: Rewrite:
\(x_{1}=-4,x_{2}=-2\)
Solve the equation \( p^{2}+14 p-38=0 \).
Solve the quadratic equation by following steps:
- step0: Solve using the quadratic formula:
\(p^{2}+14p-38=0\)
- step1: Solve using the quadratic formula:
\(p=\frac{-14\pm \sqrt{14^{2}-4\left(-38\right)}}{2}\)
- step2: Simplify the expression:
\(p=\frac{-14\pm \sqrt{348}}{2}\)
- step3: Simplify the expression:
\(p=\frac{-14\pm 2\sqrt{87}}{2}\)
- step4: Separate into possible cases:
\(\begin{align}&p=\frac{-14+2\sqrt{87}}{2}\\&p=\frac{-14-2\sqrt{87}}{2}\end{align}\)
- step5: Simplify the expression:
\(\begin{align}&p=-7+\sqrt{87}\\&p=\frac{-14-2\sqrt{87}}{2}\end{align}\)
- step6: Simplify the expression:
\(\begin{align}&p=-7+\sqrt{87}\\&p=-7-\sqrt{87}\end{align}\)
- step7: Rewrite:
\(p_{1}=-7-\sqrt{87},p_{2}=-7+\sqrt{87}\)
Here are the solutions for each equation by completing the square:
1) For the equation \( p^{2}+14 p-38=0 \):
- Completing the square gives us:
\[
p = -7 \pm \sqrt{87}
\]
- Thus, the solutions are:
\[
p_{1} = -7 - \sqrt{87}, \quad p_{2} = -7 + \sqrt{87}
\]
3) For the equation \( a^{2}+14 a-51=0 \):
- Completing the square gives us:
\[
a = -7 \pm \sqrt{100}
\]
- Thus, the solutions are:
\[
a_{1} = -17, \quad a_{2} = 3
\]
5) For the equation \( x^{2}+6 x+8=0 \):
- Completing the square gives us:
\[
x = -3 \pm \sqrt{1}
\]
- Thus, the solutions are:
\[
x_{1} = -4, \quad x_{2} = -2
\]
7) For the equation \( x^{2}+14 x-15=0 \):
- Completing the square gives us:
\[
x = -7 \pm \sqrt{64}
\]
- Thus, the solutions are:
\[
x_{1} = -15, \quad x_{2} = 1
\]
These are the solutions for each of the equations provided.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution